2021
DOI: 10.11002/kjfp.2021.28.5.663
|View full text |Cite
|
Sign up to set email alerts
|

Analytical method validation of ellagic acid as an antioxidative marker compound of the Rubus occidentalis extract

Abstract: The content of ellagic acid obtained from the extracts of Rubus occidentalis (RC) and its antioxidant activity were measured to secure basic data for developing functional materials. The extract was prepared by boiling RC in water for 3 h at 90℃. The polyphenol content and 2,2'-azinbis-(3-ethyl-benzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activity (IC 50 ) of RC was 30.60±1.27 mg/g and 176±3.95 μg/mL, respectively. RC acid hydrolysate (RCH) was analyzed using HPLC and ellagic acid as a marker com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…As a result of a study on certain cancers, ellagic acid was found to have anti-cancer effects on prostate cancer cells, cervical cancer cells, colorectal cancer cells, oral cancer cells, etc. Also, it has been reported to exhibit anti-cancer and anti-apoptotic effects in leukemia and leukemia cells (Lee et al, 2021;Mertens-Talcott & Percival, 2005;Saleem et al, 2002;Seeram et al, 2005). Although food materials derived from natural products have secured efficacy and safety through long experiences in consumption, there are differences in qualities depending on the soil, re-inhalation time, production area, and cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of a study on certain cancers, ellagic acid was found to have anti-cancer effects on prostate cancer cells, cervical cancer cells, colorectal cancer cells, oral cancer cells, etc. Also, it has been reported to exhibit anti-cancer and anti-apoptotic effects in leukemia and leukemia cells (Lee et al, 2021;Mertens-Talcott & Percival, 2005;Saleem et al, 2002;Seeram et al, 2005). Although food materials derived from natural products have secured efficacy and safety through long experiences in consumption, there are differences in qualities depending on the soil, re-inhalation time, production area, and cultivation conditions.…”
Section: Introductionmentioning
confidence: 99%